2013
DOI: 10.11613/bm.2013.043
|View full text |Cite
|
Sign up to set email alerts
|

The association of ABO blood groups with extent of coronary atherosclerosis in Croatian patients suffering from chronic coronary artery disease

Abstract: Aim:The aim of study was to: 1) examine the relationship between ABO blood groups and extent of coronary atherosclerosis in patients with chronic coronary artery disease (CAD), 2) compare ABO blood groups distribution in CAD patients and general population, 3) examine possible differences in traditional risk factors frequency in CAD patients with different ABO blood groups.Materials and methods:In the 646 chronic CAD patients (72.4% males) coronary angiograms were scored by quantitative assessment using multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
19
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 28 publications
4
19
1
Order By: Relevance
“…Conflicting reports do exist, however, with respect to ABO blood group status and its potential association with CAD. An observational study conducted between 2009 and 2010 of 646 Croatian patients with CAD (72·4% male) found no correlation between the number of coronary arteries affected as determined by angiography, or the number of segments narrowed >50%, with ABO blood group , similar to other studies . However, the study did find that blood group AB men developed CAD at a younger age than their non‐AB counterparts .…”
Section: Abh Antigens and Cardiovascular Diseasesupporting
confidence: 78%
“…Conflicting reports do exist, however, with respect to ABO blood group status and its potential association with CAD. An observational study conducted between 2009 and 2010 of 646 Croatian patients with CAD (72·4% male) found no correlation between the number of coronary arteries affected as determined by angiography, or the number of segments narrowed >50%, with ABO blood group , similar to other studies . However, the study did find that blood group AB men developed CAD at a younger age than their non‐AB counterparts .…”
Section: Abh Antigens and Cardiovascular Diseasesupporting
confidence: 78%
“…34,35 In the study of Karabuva et al, 41.33% of patients had the blood group A, 35.29% the blood group O, 16.4% the blood group B and others the AB blood group. 36 In this study, there was no relationship between ACS and blood groups, and there was no significant relationship between the number of vessels involved, the severity of vascular involvement and the type of vessel involvement with the blood groups. In a study, Capuzzo et al stated that patients without blood group O had a significant relationship with the incidence of ACS and led to clinical and subclinical progression of the disease (p=0.02).…”
Section: Discussioncontrasting
confidence: 52%
“…In patients with coronary heart disease, Gong et al found a significant relationship with Gensini [20] and non-O blood groups in Chinese population whereas Karabuva et al observed no association in Croatians [21]. Our study is also the first study investigating this association in STEMI patient population.…”
Section: Discussionsupporting
confidence: 47%